Analisis Efektivitas Pemanfaatan Kebijakan Insentif Pajak Penghasilan Final Ditanggung Pemerintah Di Masa Pandemi Covid-19 Pada Kantor Pelayanan Pajak Pratama Jakarta Pasar Rebo Tahun 2020 - Siti Humairoh; Ajat Sudrajat (Jurnal Ilmu Administrasi Publik, 2022)
The Covid-19 pandemic in Indonesia has greatly affected the national economy, many taxpayers have lost their income. Regarding the impact of Covid-19, the government provides final income tax incentives borne by the government which aims to ease the tax burden and support the efforts of taxpayers to survive during the Covid-19 pandemic. This study aims to analyze the Effectiveness of Utilization of the Government's Final Income Tax Incentive Policy during the Covid-19 Pandemic at KPP Pratama Jakarta Pasar Rebo 2020. The data collection techniques in this study were carried out by means of interviews and documentation. This research method uses a qualitative descriptive method. The results of this study indicate that the use of final income tax incentives is still not effective because there are obstacles that occur, such as many taxpayers who have not reported the realization of incentives regularly and do not understand the procedures for using tax incentives. Efforts that can be made to overcome obstacles by sending a Letter of Request for Explanation of Data and Information (SP2DK) to taxpayers who have not reported the realization of incentives and conducting more intense socialization to taxpayers.